PENGARUH PROFITABILITAS, STRUKTUR MODAL DAN PERENCANAAN PAJAK TERHADAP NILAI PERUSAHAAN - Sinurat, Vanni Basaria; Intan Pramesti Dewi (Cattleya Darmaya Fortuna, 2025)
Examining the connection between capital structure, profitability, tax planning, and company value is the primary objective of this study. Companies listed on the Indonesia Stock Exchange (BEI) in the Consumer Non-Cyclicals category from 2019 to 2023 are the subject of this quantitative analysis. Profitability, Capital Structure, and Tax Planning are the independent factors in this study, with Company Value serving as the dependent variable. The method of sampling that was used was stratified random sampling with proportionality. A total of 480 financial reports were generated from the five years of data collection from 96 different firms. Due to the presence of 139 outlier records and 130 incomplete reports, only 211 reports were deemed suitable for study after the data filtering procedure. Eviews version 12 was used to handle the data, which was analyzed using multiple linear regression and other statistical approaches.